The Effect of Hypnotherapy on Depression, Anxiety, and Stress, in People Living with HIV/AIDS, in “Friendship Plus” Peer Supporting Group, in Kediri, East Java - Ahmad Wasis Setyadi; Bhisma Murti; Argyo Demartoto (Journal of Health Promotion and Behavior, 2016)
Background: Human Immunodeficiency Virus/ Acquired Immunodeficiency Syndrome (HIV / AIDS) is a global public health problem. Identification of HIV infection can cause psychological distress to the affected, such as depression, anxiety, and stress. The deeper distress people living with HIV/AIDS (PLHIV), the weaker immunity, the stronger virus attact. This study aimed to test the effectiveness of hypnotherapy on the reducing depression, anxiety, and stress, in PLHIV at Friendship Plus peer supporting group in Kediri. Subjects and Method: This was a Randomized Controlled Trial (RCT) conducted in Kediri, East Java. A total sample of 60 PLHIV were randomized into hypnotherapy group (n1=30) and control group (n2=30). Hypnotherapy was provided 4 times per months. The levels of depression, anxiety, and stress, were measured before and after the intervention, using Depression Anxiety Stress Scale (DASS) 42, which was translated in Indonesian. The mean differences in the 3 outcome variables between the hypnotherapy and the control groups were tested by t test.Results: After the intervention, the level of the depression in the hypnotherapy group (mean= 5.07; SD= 5.45) was lower than that in the control group (mean= 17.73; SD= 6.50), and it was statistically significant (p<0.001). The level of the enxiety in the hypnotherapy group (mean= 7.70; SD= 5.29) was lower than that in the control group (mean= 20.77; SD= 5.98), and it was statistically significant (p<0.001). The level of the stress in the hypnotherapy group (mean= 7.77; SD= 6.37) was lower than that in the control group (mean= 20.30; SD= 5.34), and it was statistically significant (p<0.001). The level of DASS combined in the hypnotherapy group (mean= 20.53; SD= 15.30) was lower than that in the control group (mean= 58.80; SD= 15.63), and it was statistically significant (p<0.001).Conclusion: Hypnotherapy is effective in reducing depression, anxiety, stress, and DASS combined in PLHIV.Keywords: depression, anxiety, stress, DASS, PLHIVCorrespondence: Ahmad Wasis Setyadi. Masters Program in Public Health, Sebelas Maret University, Indonesia. Email: ahmadwasis@gmail.com.Journal of Health Promotion and Behavior (2016), 1(2): 99-108https://doi.org/10.26911/thejhpb.2016.01.02.05